Determination of the binding site size of hexaammineruthenium(iii) inside monolayers of DNA on gold. Issue 2 (9th November 2020) - Abi, Alireza; Safavi, Afsaneh
Abstract : Hexaammineruthenium(iii ) metal complex can bind to surface-tethered DNA strands in excess of what is required for the compensation of the DNA charges. Abstract : Hexaammineruthenium(iii ), RuHex 3+, is a DNA-binding metal complex that is widely used as a redox marker for the indirect determination of DNA coverage at the electrode surface. The conversion of electrochemically quantifiable surface excess of RuHex 3+ into DNA surface coverage requires the knowledge of the binding site size of RuHex 3+ ( s ). Traditionally, s on surface-immobilized DNA has been assumed to be equivalent to that on solution-phase DNA, which was experimentally determined in previous studies. Nevertheless, the different local microenvironments existing inside DNA monolayers in comparison to that in bulk solutions cast doubt on the validity of this assumption. In this report, we used electrochemical techniques to investigate s on surface-immobilized DNA. The values of s inside the DNA monolayers were found to be significantly smaller than that reported on solution-phase DNA. Besides, s was found to depend on the DNA packing density and became larger by increasing the DNA surface coverage or hybridizing the surface-tethered DNAs with complementary strands. Our data indicate that the RuHex 3+ method, in which an s value of 3 nucleotides is used for the conversion of RuHex 3+ to DNA surface coverage, does not always give reliable results.